The Use of National and Regional Languages in the EFL Teaching at SMPN 1 Salem, Brebes District - Savitri, Ayu Ida; Chandra, Oktiva Herry; Marlina, Neneng (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
EFL Teaching is performed by applying various teaching methodologies to suit the characteristics and needs of the students. For the EFL students at public junior high schools who did not experience English learning in public elementary schools and have limited or no prior English language experience, the EFL teacher may incorporate the students’ acquired languages to help them understand the materials. The research exposes why an EFL teacher at SMPN 1 Salem, integrates national and regional languages in her EFL classroom. The data were collected by giving questionnaires to 27 students and 1 teacher. The results show that the teacher mostly incorporates Indonesian and Sundanese with English in her classroom. Javanese is not used, as all students speak it as their mother tongue, even though they belong to Salem Sub-District, Brebes District, Central Java Province, whose regional language is Javanese. The three languages are used in the classroom to enable students to master English, as it is quite difficult to acquire when it is fully taught in English. The research reveals how teacher adapts to the classroom conditions